2007
DOI: 10.1159/000100780
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Functional Decline in Nonagenarians: A One-Year Follow-Up

Abstract: Background: Disability and a decline in functional capacity are common in old age. Objective: To determine predictors of functional decline in nonagenarians’ basic activities of daily living (ADL) after 1 year of follow-up. Methods: A sample of 97 nonagenarians subjects not previously severely dependent (Barthel Index >59) was evaluated. This sample included 72 women (74.2%) and the mean (SD) age was 93.4 ± 2.7 years. The following data were collected: sociodemographic data, Barthel Index (BI), Lawton-Brody In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
2
11
0
1
Order By: Relevance
“…As we all knew, advanced age is probably one of the most important factor related to functional decline, even some studies suggest the increase in relative risk of functional loss is about 2.0 for each 10-year increase in age [28]. However, in Formiga’s study, age lost the association with ADL disability in nonagenarian population [29]. In this study, we demonstrated a consistent and graded association between the increase of age and likelihood of disability in ADL/IADL just like the quantity of chronic conditions, and exponential relationship even displayed a dramatic increase among nonagenarian population.…”
Section: Discussionmentioning
confidence: 99%
“…As we all knew, advanced age is probably one of the most important factor related to functional decline, even some studies suggest the increase in relative risk of functional loss is about 2.0 for each 10-year increase in age [28]. However, in Formiga’s study, age lost the association with ADL disability in nonagenarian population [29]. In this study, we demonstrated a consistent and graded association between the increase of age and likelihood of disability in ADL/IADL just like the quantity of chronic conditions, and exponential relationship even displayed a dramatic increase among nonagenarian population.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from the acute care setting reported severe but reversible functional changes within a few months and proved that MNA‐LF scores and the former MNA‐SF categorization were able to predict the predefined functional decline . In two studies with community‐dwelling subjects aged 90 and older, MNA‐SF scores failed to predict 1‐ and 2‐year functional decline . Another study investigated 4‐year functional decline in a population‐based sample of older Taiwanese adults and compared the MNA forms based on sum scores.…”
Section: Discussionmentioning
confidence: 99%
“…The relation between the impairments of basic activities of daily living and instrumental activities of daily living and cardiovascular co-morbidities has not been extensively studied[20,21]. Maugeri et al related several parameters (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated significant functional disability in those individuals with heart failure, whereas individuals with preserved systolic LV function obtained better scores in the tests[21]. In contrast, Formiga et al evaluated the predictors of functional decline in 97 nonagenarians at 1 year follow-up and identified a history of stroke as an independent risk factor whereas the history of ischemic cardiomyopathy or heart failure were not related to functional decline[20]. …”
Section: Discussionmentioning
confidence: 99%